2018
DOI: 10.1177/2156759x18820331
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Job Duties That Impact School Counselor Wellness: The Role of RAMP, Supervision, and Support

Abstract: The authors examined the predictive relationship between the performance of job duties informed by the American School Counselor Association (ASCA) National Model and overall wellness of school counselors. We also examined the relationship between organizational factors (i.e., Recognized ASCA Model Program, supervision, and support), the frequency of job duties performed, and overall wellness. The results revealed a predictive relationship between some of the job duties school counselors perform and wellness. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 41 publications
4
29
1
Order By: Relevance
“…Establishing an organizational culture that is supportive and responsive to the needs of the school counselor often means developing the skills for creating positive school climates and supportive professional relationships (Clemens et al, 2009). School counselors are expected to play an active role in effectively advocating for the type of job resources and supports that not only promote their own wellness, but also enhance the quality of services for their students (Randick et al, 2018). Preventing burnout for school counselors may therefore rest on a combination of activating essential organizational supports, addressing high demands that serve as a hindrance to effectively performing their roles, and tapping into personal strengths and resources that can promote vitality and engagement in a challenging but rewarding profession.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing an organizational culture that is supportive and responsive to the needs of the school counselor often means developing the skills for creating positive school climates and supportive professional relationships (Clemens et al, 2009). School counselors are expected to play an active role in effectively advocating for the type of job resources and supports that not only promote their own wellness, but also enhance the quality of services for their students (Randick et al, 2018). Preventing burnout for school counselors may therefore rest on a combination of activating essential organizational supports, addressing high demands that serve as a hindrance to effectively performing their roles, and tapping into personal strengths and resources that can promote vitality and engagement in a challenging but rewarding profession.…”
Section: Discussionmentioning
confidence: 99%
“…In the surveys, the counselors emphasized the positive effect of their choice and persistence in the occupation of school counseling and that the occupation is a response to their personality and psychological needs (Erhard, 1998(Erhard, , 2008. Also Randick, Dermer and Michel (2019) found that school counselors in the US, appear to enjoy duties that are self-driven, collaborative, action oriented, and results driven. These characteristics are captured by coordination duties such as coordination of interventions with students, parents, teachers, and other significant stakeholders.…”
Section: (B) Professional Identity As Reflected By Satisfactionmentioning
confidence: 99%
“…For example, one coordinator wrote, ‘I’m also energized by observing colleagues doing the same work that I do and exchanging ideas/sharing resources’. This feeling of having a strong, supportive learning community and professional network is significant, due to the important positive impact that peer support has on school counselor job satisfaction (Randick et al, 2018), and, in turn, on service delivery to students (Mullen & Gutierrez, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to administrative support, team support (Collins, 2007; Lloyd et al, 2002) and help with facilitating communication between staff (Pyne, 2011) have also been linked to increased social work and school counselor job satisfaction. Furthermore, sufficient training and supervisory support from district and peers have been found to predict job satisfaction (Baggerly & Osborn, 2006; Randick et al, 2018) and reduce burnout (Holman et al, 2019; Moyer, 2011) in both social workers and school counselors. More broadly, feeling valued (Agresta, 2006) and feeling as if their role matters to those they work with (Hamama, 2012; Rayle, 2006) are also important factors that contribute to job satisfaction for both professions.…”
Section: Professional Experiences Of School Counselors and School Socmentioning
confidence: 99%